Macrophage Delivered HSV1716 Is Active against Triple Negative Breast Cancer - Amy Kwan; Faith Howard; Natalie Winder; Emer Atkinson; Ameera Jailani; Priya B. Patel; Richard Allen; Penelope D. Ottewell; Gary C. Shaw; Joe Conner; Caroline Wilson; Sanjay K. Srivastava; et al. (Future Pharmacology, 2022)
Oncolytic viruses (OV) promote anti-tumour responses through the initiation of immunogenic cancer cell death which activates the host’s systemic anti-tumour immunity. We have previously shown that intravenously administered HSV1716 is an effective treatment for mammary cancer. However, intravenous administration of a virus has the potential to result in neutralization and sequestration of the virus which may reduce efficacy. Here, we show that the oncolytic virus HSV1716 can be administered within a cellular carrier (macrophages). PyMT and 4T1 murine mammary cancer cell lines were implanted into immuno-competent murine models (orthotopic primary, early metastatic and brain metastasis models). HSV1716 or macrophages armed with HSV1716 (M-HSV1716) were administered intravenously, and tumour size was quantified using caliper measurement or bioluminescence imaging. Administration of M-HSV1716 led to tumour shrinkage and increased the survival of animals. Furthermore, these results were achieved with a 100-fold lower viral load, which has the potential for decreased toxicity. Our results demonstrate that M-HSV1716 is associated with activity against murine mammary cancers and provides an alternative platform for the systemic delivery of OV.